ANALISIS PENGARUH PERTUMBUHAN EKONOMI TERHADAP KEMISKINAN TINGKAT PROVINSI DI INDONESIA - Fenny Linsisca Putri; Oktavia Dwi Megawati; Yufis Azhar (Universitas Methodist Indonesia, 2020)
This study aims to determine what causes or impacts economic growth in poverty in Indonesia from 2013 to 2018. Economic growth and poverty are very important in seeing the success of a country's development. However, developing countries that are experiencing economic growth such as Indonesia are also accompanied by an increase in the growth of the population living under poverty. Therefore, poverty is also one of the problems in the economy in Indonesia which is complex and multidimensional. In this study, to see how much influence economic growth has on the number of poor people, a simple linear regression is used. The conclusion obtained from this process is that variable X (economic growth) has an influence on variable Y (number of poor people in Indonesia), especially at the provincial level. Simultaneously, economic growth has an influence on the poverty rate in Indonesia by 3,485, while the coefficient is 1,359.